Students’ performance in blended learning: disciplinary difference and instructional design factors - Vo, Minh Hien; Zhu, Chang; Diep, Anh Nguyet (Journal of computers in education (the official journal of the Global Chinese Society for Computers in Education), 2020)
Significant enhancement in students’ learning performance has been noticed in blended learning courses. Yet, the differential effect of blended learning as a function of disciplinary difference has not widely been explored. Moreover, studies on the critical factors related to students’ performance measured by objective course grades are recognized to a lesser extent compared with those using self-reported or perceived learning achievement. In the present study, the effect of blended learning in hard and soft courses is discerned. Factors related to students’ performance measured by final course grades are unraveled, controlling for the effects of gender and prior learning achievement. The participants ( N = 571) are students following blended learning courses at a public university in Vietnam. A questionnaire is employed to collect data, which is subject to confirmatory factor analysis and hierarchical regression analyses. The results show that students in soft disciplines obtain higher grades than peers in hard disciplines. Clear goals and expectations, material quality, and collaborative learning are significant predictors of students’ performance.